Actinobacillus actinomycetemcomitans serotype b-specific polysaccharide antigen stimulates production of chemotactic factors and inflammatory cytokines by human monocytes. - Yamaguchi, N (1996)
Serotype b-specific polysaccharide antigen (SPA) was extracted from whole cells of Actinobacillus actinomycetemcomitans Y4 by autoclaving and purified by chromatography on DEAE-Sephadex A-25 and Sephacryl S-300. SPA induced the release of monocyte and leukocyte chemotactic factors by human monocytes. Polymyxin B had almost no effect on the release of monocyte chemotactic factor, but a monoclonal antibody against SPA markedly inhibited it. Human monocytes stimulated with SPA exhibited the increased mRNA expression of monocyte chemoattractant protein 1 (MCP-1) and a neutrophil chemotactic factor, interleukin-8 (IL-8). On the other hand, SPA induced the release of IL-1, IL-6, and tumor necrosis factor (TNF) and enhanced the expression of IL-1alpha, IL-1beta, IL-6, and TNF alpha (TNF-alpha) mRNAs. Human monocytes expressed MCP-1 and IL-8 mRNAs when stimulated by human recombinant IL-1alpha, I1-1beta, IL-6, and TNF-alpha, suggesting that these inflammatory cytokines induced by SPA might participate in the production of chemotactic factors in human monocytes.